PENERAPAN E-MODUL LARUTAN PENYANGGA BERBASIS PROBLEM BASED LEARNING TERINTEGRASI TEACHING AT THE RIGHT LEVEL UNTUK MENINGKATKAN HASIL BELAJAR MURID FASE F DI SMAN 9 PADANG - Fatimah; Iryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Buffer solutions are one of the more abstract and complex topics in chemistry because they involve the interplay of macroscopic, microscopic, and symbolic representations, and require the ability to analyze and calculate pH. Based on interviews with chemistry teachers at SMAN 9 Padang, it was found that in the 2024/2025 academic year, 45% of 11th-grade students had not met the Learning Objective Achievement Criteria (KKTP) for the topic of buffer solutions. One effort to address this issue is the implementation of a Problem-Based Learning (PBL)-based e-module on buffer solutions integrated with Teaching at the Right Level (TaRL). This study aims to analyze the effect of implementing a PBL-based e-module on buffer solutions integrated with TaRL on the cognitive learning outcomes of Phase F students at SMAN 9 Padang. This study employed a quasi-experimental method with a nonequivalent control group design. The research sample consisted of Class XI Moving Chemistry 4 as the experimental class and Class XI Moving Chemistry 5 as the control class, both selected using purposive sampling. The research instrument consisted of a 15-item multiple-choice objective test administered before (pretest) and after (posttest) instruction. The results showed that the average posttest score for the experimental class (80.44) was higher than that of the control class (67.56). The average N-gain score for the experimental class was 0.744, which falls into the high category, while that of the control class was 0.568, which falls into the moderate category. The independent samples t-test yielded a t-value of 4.53. Thus, the PBL-based buffer solution e-module integrated with TaRL can improve students’ cognitive learning outcomes.